Finite-difference time-domain analysis of integrated ceramic ball grid array package antenna for highly integrated wireless transceivers - Zhang, Yue Ping (2009)
This paper presents a study of the integration of an antenna in a ceramic ball grid array package for highly integrated wireless transceivers. The study has been carried out on an 11 X 11.66 mm2 small microstrip antenna in a thin 48-ball ceramic ball grid array package with the finite-difference time-domain (FDTD) method in C band. The impedance and radiation characteristics of the antenna are examined. More importantly, the loading effects of the complementary metal–oxide–semiconductor (CMOS) chip and bond wires on the performance of the antenna are investigated. It is found that the loading generally increases the impedance bandwidth but decreases the radiation efficiency of the antenna. To minimize detrimental loading, the shield of the antenna from the CMOS chip is considered. A new design has been realized. The new antenna achieves impedance bandwidth of 4.65%, radiation efficiency of 63%, and gain of 5.6 dBi at 5.52 GHz.